2022
DOI: 10.1159/000524789
|View full text |Cite
|
Sign up to set email alerts
|

AGO Recommendations for the Diagnosis and Treatment of Patients with Locally Advanced and Metastatic Breast Cancer: Update 2022

Abstract: The Breast Committee of the Arbeitsgemeinschaft Gynäkologische Onkologie (German Gynecological Oncology Group, AGO) presents the 2022 update of the evidence-based recommendations for the diagnosis and treatment of patients with locally advanced and metastatic breast cancer (MBC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…The currently recommended first-line treatment for patients with HER2-positive metastatic disease is a taxane in combination with dual HER2 blockade using trastuzumab and pertuzumab [6–9]. This therapy was established as a standard of care by the phase III CLEOPATRA trial, which showed that the addition of pertuzumab to the combination of docetaxel and trastuzumab resulted in a significantly longer OS [57.1 (95% confidence interval (CI) 50–72) vs. 40.8 (95% CI 36–48) months, respectively] [2 ▪ ].…”
Section: First-line Treatmentmentioning
confidence: 99%
See 4 more Smart Citations
“…The currently recommended first-line treatment for patients with HER2-positive metastatic disease is a taxane in combination with dual HER2 blockade using trastuzumab and pertuzumab [6–9]. This therapy was established as a standard of care by the phase III CLEOPATRA trial, which showed that the addition of pertuzumab to the combination of docetaxel and trastuzumab resulted in a significantly longer OS [57.1 (95% confidence interval (CI) 50–72) vs. 40.8 (95% CI 36–48) months, respectively] [2 ▪ ].…”
Section: First-line Treatmentmentioning
confidence: 99%
“…Both antibodies are continued until disease progression, and, in case of positive hormone receptor status, endocrine therapy is added after discontinuation of chemotherapy. Due to favorable toxicity and efficacy reported in phase II trials, weekly paclitaxel is a widely accepted alternative to docetaxel in this setting [6–8]. If patient preferences, poor performance status, or relevant comorbidities preclude the use of chemotherapy in patients with hormone receptor (HR)-positive HER2-positive disease, endocrine therapy in combination with anti-HER2 treatment may be used [6,8].…”
Section: First-line Treatmentmentioning
confidence: 99%
See 3 more Smart Citations